High-friction-voltage hydroxyethyl cellulose sensing material and preparation method thereof
By designing a three-layer structure high friction voltage hydroxyethyl cellulose sensing material, the problems of insufficient mechanical strength, friction performance and charge maintenance of traditional materials are solved, and efficient nano friction power generation is achieved, which improves the stability of the equipment and Service life.
Patent Information
- Application Number
- CN202411229091.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-03
AI Technical Summary
Traditional friction nano-powered power generation materials lack mechanical strength, friction performance and charge maintenance, resulting in reduced power generation efficiency and equipment damage, limiting their application potential.
Design a three-layer structure with high friction voltage hydroxyethyl cellulose sensing material, using the upper to lower structures as the upper hydroxyethyl cellulose film, polyvinylidene fluoride film and the lower hydroxyethyl cellulose film, through Preparation by casting method and electrospinning technology, a three-dimensional intercalation structure is formed to enhance mechanical and electrical properties.
It significantly improves the efficiency and stability of nano friction power generation, improves the structural stability and charge transfer efficiency of the material, extends the service life of the equipment, and enhances the output stability and sensitivity of the friction generator.
Smart Images

Figure CN119116489A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nano friction power generation sensing technology and membrane material manufacturing, and specifically to a high friction voltage hydroxyethyl cellulose sensing material and a preparation method thereof. Background Art
[0002] With the surge in demand for sustainable energy and efficient sensors, triboelectric nanopower generation, as a new energy conversion technology, collects mechanical energy and converts it into electrical energy by utilizing the friction charge effect generated when two different materials come into contact, separate or slide, showing great application potential. Compared with traditional energy conversion methods, TENG has the advantages of high voltage and low current, simple structure, low cost, environmental friendliness, and the ability to convert tiny mechanical energy in daily life into electrical energy, providing new energy solutions for the Internet of Things, wearable devices, environmental monitoring and other fields.
[0003] However, the deficiencies of traditional materials in mechanical strength, friction performance and charge retention limit their application potential. For example, under high-intensity or frequent mechanical stress, many traditional materials are prone to fatigue fracture or deformation, resulting in reduced power generation efficiency or even equipment damage. Ideal TENG materials should have a high friction coefficient to generate more charges, and also have good wear resistance to extend service life.
[0004] Hydroxyethyl cellulose (HEC) has become a potential material for high-performance TENG films due to its good biocompatibility, strong processability and excellent film-forming properties, which can improve triboelectric performance and durability. Polyvinylidene fluoride (PVDF) is used as a charge retention phase, with a high dielectric constant and significant piezoelectric effect, which enhances the charge storage and electrical output performance of TENG. At the same time, its insulation reduces charge leakage and improves conversion efficiency.
[0005] The present invention innovatively combines the advantages of HEC and PVDF to design a three-layer structure sensing material: HEC film is the upper and lower layers, and PVDF film is the middle layer, forming a three-dimensional intercalation structure. This design not only takes advantage of the triboelectric properties of HEC and the high dielectric properties of PVDF, but also enhances the mechanical and electrical properties through multi-layer composites, opening up a new path for the preparation of high-performance TENG devices. Summary of the invention
[0006] In view of the problems that traditional materials are insufficient in mechanical strength, friction performance and charge retention, the present invention provides a method for preparing a high friction voltage hydroxyethyl cellulose sensing material.
[0007] The present invention is achieved through the following technical solutions:
[0008] A high friction voltage hydroxyethyl cellulose sensing material comprises a three-layer structure, which comprises, from top to bottom, an upper hydroxyethyl cellulose film, a polyvinylidene fluoride film and a lower hydroxyethyl cellulose film.
[0009] A method for preparing a high friction voltage hydroxyethyl cellulose sensing material comprises the following steps:
[0010] Step 1, preparing a mixed dispersion of hydroxyethyl cellulose and aramid nanofibers and a spinning solution containing polyvinylidene fluoride;
[0011] Step 2, the mixed dispersion of hydroxyethyl cellulose and aramid nanofibers is cast and dried to obtain a lower hydroxyethyl cellulose film;
[0012] The spinning solution containing polyvinylidene fluoride is spun by electrostatic spinning to obtain a polyvinylidene fluoride film;
[0013] Step 3, placing a polyvinylidene fluoride film on the upper surface of the dried lower hydroxyethyl cellulose film; then, on the upper surface of the polyvinylidene fluoride film, using a casting method to prepare a wet upper hydroxyethyl cellulose film from a mixed dispersion of hydroxyethyl cellulose and aramid nanofibers; and then drying to obtain a three-dimensional intercalated HEC-PVDF-HEC high friction voltage sensing material.
[0014] Preferably, in step 1, the preparation method of the mixed dispersion of hydroxyethyl cellulose and aramid nanofibers is as follows: dissolving 2 to 3 g of hydroxyethyl cellulose powder in 200 to 300 mL of aramid nanofiber dispersion at 45 to 55° C. for 20 to 30 min to obtain a mixed dispersion of hydroxyethyl cellulose and aramid nanofibers; wherein the viscosity of the hydroxyethyl cellulose is 2600 to 3300 mPa.s, and the concentration of the hydroxyethyl cellulose dispersion is 0.010 to 0.015 g / mL.
[0015] Preferably, the aramid nanofiber mixed dispersion is prepared as follows: first, an alkaline solution, para-aramid fibers and dimethyl sulfoxide are stirred and mixed to obtain a dispersion A; wherein the mass ratio of the para-aramid fibers to the dimethyl sulfoxide is 2-3:200-300, the solute of the alkaline solution is potassium hydroxide, the concentration of the solute in the alkaline solution is 0.3-0.6 g / mL, and the ratio of the alkaline solution to the para-aramid fibers is 1-2 mL:2-3 g;
[0016] Dispersion A is evenly dispersed in deionized water, and then filtered to obtain para-aramid nanofiber dispersion B; wherein the volume ratio of water to dispersion A is 1000-1500:50-100, and the concentration of the para-aramid nanofiber dispersion is 1%-1.5%.
[0017] Preferably, in step 1, the spinning solution containing polyvinylidene fluoride is prepared as follows: the spinning solution is obtained by dissolving polyvinylidene fluoride in N,N-dimethylformamide solution.
[0018] Preferably, the ratio of polyvinylidene fluoride to N,N-dimethylformamide solution is 4-5 g:7-9 mL, the dissolution temperature is 60-70° C., the rotation speed is 100-200 r / min, and the time is 2-3 h.
[0019] Preferably, in step 2, during the preparation of the lower hydroxyethyl cellulose film, the drying temperature is 60-70° C., the drying time is 10-12 h, and the film thickness of the lower hydroxyethyl cellulose film after drying is 0.06-0.08 mm.
[0020] Preferably, in step 2, during the electrospinning process, the voltage is 15-17 kV, the temperature is 35-45° C., the humidity is 65%-75%, the spinning liquid spinning rate is 0.008-0.010 mL / min, and the time is 6-8 h.
[0021] Preferably, in step 3, during the drying process, the temperature is 60-70° C., the time is 10-12 hours, and the film thickness of the upper hydroxyethyl cellulose film after drying is 0.06-0.08 mm.
[0022] A grid-structured friction nano-power generation device prepared from the high friction voltage hydroxyethyl cellulose sensing material.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] First, a high friction voltage hydroxyethyl cellulose sensing material of the present invention is prepared by a phase-oriented assembly strategy, and a wide bandgap charge retention phase polyvinylidene fluoride electrospinning film is introduced into a friction phase hydroxyethyl cellulose film through a carefully designed three-dimensional intercalation (HEC-PVDF-HEC). The three-dimensional intercalation (HEC-PVDF-HEC) structure sandwiches a layer of polyvinylidene fluoride film (PVDF) by two layers of hydroxyethyl cellulose film (HEC), realizing the organic combination of electrostatic coupling and charge storage, wherein the HEC layer provides good electrostatic coupling induction and friction power generation capabilities, and the PVDF layer serves as a charge retention phase, effectively improving the accumulation and transmission efficiency of the charge. This structural design not only enhances the structural stability of the material, but also optimizes the charge transmission and retention path, significantly improves the efficiency and stability of nano friction power generation, and also improves the output stability and sensitivity of the nano friction generator.
[0025] Secondly, after long-term experiments, the present invention prefers hydroxyethyl cellulose (HEC) as the contact friction layer, which has the advantages of (1) good solubility and non-ionicity: HEC can be dissolved and dispersed in aqueous solvents, and has low cost and wide sources, which is convenient for large-scale processing, production and application; (2) Hydroxyethyl cellulose (HEC) is composed of a cellulose main chain and a hydroxyethyl side chain structure. It is a water-soluble polymer compound prepared by etherification reaction of cellulose with ethylene oxide (or chloroethanol). The surface is rich in hydroxyl groups, which help to attract charge transfer in electrostatic coupling induction and have the inherent advantage of preparing high friction voltage positive electrode materials; (3) HEC has good biocompatibility and degradability, and is degradable, renewable, and green and environmentally friendly, which makes HEC-based nano-friction power generation sensor materials have potential application advantages in the biomedical field, such as wearable medical devices.
[0026] Next, polyvinylidene fluoride (PVDF) was used to prepare the positive electrode material for nano-frigoelectric sensors. Its advantages in charge retention phase are: (1) PVDF's unique molecular structure and dipole arrangement enable PVDF to generate stronger electrical signals when subjected to external forces, more effectively convert mechanical energy into electrical energy, and generate and retain more charges during friction; (2) The fluorine atoms in the PVDF molecular chain have strong electronegativity, and the CF bonds formed with carbon atoms have high stability and polarity. This polarity enables PVDF molecules to generate dipoles when subjected to external forces and form a stable electric field inside the material, which is conducive to the accumulation and stability of charges. (3) PVDF can resist erosion by a variety of environmental factors (such as humidity, temperature, acid and alkali, etc.), so that PVDF-based positive electrode materials can still maintain stable charge retention performance in harsh environments, thereby extending the service life of nano-frigoelectric sensors.
[0027] Furthermore, the introduction of aramid nanofibers to prepare the positive electrode material of nano-frictional power generation sensors has the following advantages: (1) Excellent mechanical properties: Aramid nanofibers are not easily deformed when the macromolecular chains composed of benzene rings and amide groups present a linear rigid straight chain configuration, and have the characteristics of high strength and high modulus. They are combined with HEC to form a composite film, which improves the overall mechanical properties and friction properties of the material through stress transfer; (2) Aramid nanofibers have the characteristics of high temperature resistance and corrosion resistance, and maintain stable frictional power generation performance in a wide temperature range and harsh chemical environment. (3) Aramid nanofibers can form a good interface with a variety of matrix materials, which helps to reduce the leakage and loss of charge at the interface and improve the frictional power generation and charge retention performance of the positive electrode material.
[0028] Furthermore, the present invention introduces aramid nanofibers into the HEC matrix by dissolving and blending, which significantly improves the strength and toughness of the composite material. At the same time, the addition of nanofibers also increases the specific surface area of the material, which is conducive to the generation and transfer of friction charges, and further improves the output performance of the friction nanogenerator.
[0029] Furthermore, the present invention adopts the casting method to prepare HEC film, and the process accurately controls the drying temperature and time, which has the advantage of being scalable. At the same time, when preparing PVDF film, the present invention adopts electrostatic spinning technology, optimizes the parameters such as spinning solution ratio, spinning voltage, and drum rotation speed, and the prepared PVDF film has the advantages of wide band gap and high specific surface area, which provides a strong guarantee for the preparation of high-performance nano friction power generation sensor positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a structural diagram of a high friction voltage hydroxyethyl cellulose sensing material of the present invention;
[0031] Figure 2 It is a flow chart of a method for preparing a high friction voltage hydroxyethyl cellulose sensing material of the present invention;
[0032] Figure 3 This is the friction voltage of the high friction voltage hydroxyethyl cellulose sensing material prepared in Example 1 of the present invention.
[0033] Figure 4 This is the friction voltage of the high friction voltage hydroxyethyl cellulose sensing material prepared in Example 2 of the present invention.
[0034] Figure 5 This is the friction voltage of the high friction voltage hydroxyethyl cellulose sensing material prepared in Example 3 of the present invention.
[0035] Figure 6 The friction voltage of the high friction voltage hydroxyethyl cellulose sensing material prepared in Example 4 of the present invention;
[0036] Figure 7 This is the friction voltage of the high friction voltage hydroxyethyl cellulose sensing material prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0038] The invention discloses a high friction voltage hydroxyethyl cellulose sensing material, comprising a three-layer structure, which comprises an upper hydroxyethyl cellulose film, a polyvinylidene fluoride film and a lower hydroxyethyl cellulose film from top to bottom.
[0039] The present invention also discloses a method for preparing a high friction voltage hydroxyethyl cellulose sensing material, referring to Figure 2 , including the following steps:
[0040] Step 1, preparing a mixed dispersion of hydroxyethyl cellulose and aramid nanofibers and a spinning solution containing polyvinylidene fluoride.
[0041] The preparation of the aramid nanofiber mixed dispersion is as follows: first, an alkaline solution, para-aramid fibers and dimethyl sulfoxide are stirred and mixed to obtain a dispersion A; wherein the mass ratio of the para-aramid fibers to the dimethyl sulfoxide is 2-3:200-300, the solute of the alkaline solution is potassium hydroxide, the concentration of the solute in the alkaline solution is 0.3-0.6 g / mL, and the ratio of the alkaline solution to the para-aramid fibers is 1-2 mL:2-3 g;
[0042] Dispersion A is evenly dispersed in deionized water, and then filtered to obtain para-aramid nanofiber dispersion B; wherein the volume ratio of water to dispersion A is 1000-1500:50-100, and the concentration of the para-aramid nanofiber dispersion is 1%-1.5%.
[0043] The preparation method of the mixed dispersion of hydroxyethyl cellulose and aramid nanofibers is as follows: at 45 to 55° C., 2 to 3 g of hydroxyethyl cellulose powder is dissolved in 200 to 300 mL of aramid nanofiber dispersion for 20 to 30 min to obtain a mixed dispersion of hydroxyethyl cellulose and aramid nanofibers; wherein the viscosity of the hydroxyethyl cellulose is 2600 to 3300 mPa.s, and the concentration of the hydroxyethyl cellulose dispersion is 0.010 to 0.015 g / mL.
[0044] The spinning solution containing polyvinylidene fluoride is prepared as follows: the polyvinylidene fluoride is dissolved in N, N-dimethylformamide solution to obtain the spinning solution, wherein the ratio of polyvinylidene fluoride to N, N-dimethylformamide solution is 4-5 g: 7-9 mL, the dissolution temperature is 60-70° C., the rotation speed is 100-200 r / min, and the time is 2-3 h.
[0045] Step 2, the mixed dispersion of hydroxyethyl cellulose and aramid nanofibers is subjected to a casting method combined with drying to obtain a lower layer of hydroxyethyl cellulose film; wherein the drying temperature is 60-70° C., the drying time is 10-12 hours, and the film thickness is 0.06-0.08 mm.
[0046] A spinning solution containing polyvinylidene fluoride is electrospun to obtain a polyvinylidene fluoride film; wherein, during the electrospinning process, the voltage is 15-17 kV, the temperature is 35-45° C., the humidity is 65%-75%, the spinning solution spinning rate is 0.008-0.010 mL / min, and the time is 6-8 hours.
[0047] Step 3, placing the polyvinylidene fluoride film on the upper surface of the dried lower hydroxyethyl cellulose film, and the two can be attached at this time; then, on the upper surface of the polyvinylidene fluoride film, the hydroxyethyl cellulose and aramid nanofiber mixed dispersion liquid is cast to prepare a wet upper hydroxyethyl cellulose film; then drying at 60-70°C for 10-12h, the dried upper hydroxyethyl cellulose film, the polyvinylidene fluoride film and the lower hydroxyethyl cellulose film are automatically bonded after drying, thereby obtaining a three-dimensional intercalated HEC-PVDF-HEC high friction voltage sensing material. Among them, the thickness of the upper hydroxyethyl cellulose film and the lower hydroxyethyl cellulose film is the same, the thickness of the hydroxyethyl cellulose and aramid nanofiber mixed dispersion liquid poured into the mold before drying is 8-10mm, and after drying, the film thickness of the two after drying is 0.06-0.08mm.
[0048] Example 1
[0049] Step 1, dissolving 2 g of hydroxyethyl cellulose powder in 200 mL of aramid nanofiber dispersion at 55° C. for 25 min to obtain a 0.01 g / mL hydroxyethyl cellulose and aramid nanofiber mixed dispersion;
[0050] At 70°C, 4 g of polyvinylidene fluoride was dissolved in 9 mL of N,N-dimethylformamide solution and stirred at 200 r / min for 3 h to prepare the spinning solution for the electrospinning membrane.
[0051] Step 2, pouring the dispersion evenly into a polytetrafluoroethylene mold, and drying in a hot oven at 60° C. for 12 h to obtain a lower layer of hydroxyethyl cellulose film;
[0052] The spinning solution of the electrospinning membrane is electrospun to obtain a polyvinylidene fluoride film, at which the voltage is 15.5 KV, the temperature is 35°C, the humidity is 65%, the spinning solution spinning rate is 0.008 mL / min, and the spinning time is 6 hours;
[0053] Step 3, gluing a polyvinylidene fluoride film on the lower hydroxyethyl cellulose film, and continuing to pour a 10 mm thick mixed dispersion of hydroxyethyl cellulose and aramid nanofibers to obtain a wet upper hydroxyethyl cellulose film, drying in a hot oven at 60° C. for 12 hours, and finally drying to obtain a three-dimensional intercalated HEC-PVDF-HEC high friction voltage sensing material.
[0054] Example 2
[0055] Step 1, dissolving 2.5 g of hydroxyethyl cellulose powder in 200 mL of aramid nanofiber dispersion at 55° C. for 30 min to obtain a 0.0125 g / mL hydroxyethyl cellulose and aramid nanofiber mixed dispersion;
[0056] At 70°C, 4 g of polyvinylidene fluoride was dissolved in 9 mL of N,N-dimethylformamide solution and stirred at 200 r / min for 3 h to prepare the spinning solution for the electrospinning membrane.
[0057] Step 2, pouring the dispersion evenly into a polytetrafluoroethylene mold, and drying in a hot oven at 60° C. for 12 h to obtain a lower layer of hydroxyethyl cellulose film;
[0058] The spinning solution of the electrospinning membrane is electrospun to obtain a polyvinylidene fluoride film, at which the voltage is 15.5 KV, the temperature is 35° C., the humidity is 65%, the spinning solution spinning rate is 0.010 mL / min, and the spinning time is 6 h;
[0059] Step 3, gluing a polyvinylidene fluoride film on the lower hydroxyethyl cellulose film, and continuing to cast a 10 mm thick mixed dispersion of hydroxyethyl cellulose and aramid nanofibers to obtain a wet upper hydroxyethyl cellulose film, and then drying it in a hot oven at 60° C. for 12 hours, and finally drying to obtain a three-dimensional intercalated HEC-PVDF-HEC high friction voltage sensing material.
[0060] Example 3
[0061] Step 1, dissolving 3 g of hydroxyethyl cellulose powder in 200 mL of aramid nanofiber dispersion at 55° C. for 30 min to obtain a 0.015 g / mL hydroxyethyl cellulose and aramid nanofiber mixed dispersion;
[0062] At 70°C, 4.0 g of polyvinylidene fluoride was dissolved in 9 mL of N,N-dimethylformamide solution and stirred at 200 r / min for 3 h to prepare the spinning solution for the electrospinning membrane.
[0063] Step 2, pouring the dispersion evenly into a polytetrafluoroethylene mold, and drying in a hot oven at 60° C. for 12 h to obtain a lower layer of hydroxyethyl cellulose film;
[0064] The spinning solution of the electrospinning membrane is electrospun to obtain a polyvinylidene fluoride film, at which the voltage is 15.5 KV, the temperature is 35° C., the humidity is 65%, the spinning solution spinning rate is 0.010 mL / min, and the spinning time is 6 h. The polyvinylidene fluoride film is obtained by electrospinning;
[0065] Step 3, gluing a polyvinylidene fluoride film on the lower hydroxyethyl cellulose film, and continuing to cast a 10 mm thick mixed dispersion of hydroxyethyl cellulose and aramid nanofibers to obtain a wet upper hydroxyethyl cellulose film, drying in a hot oven at 60° C. for 12 h, and finally drying to obtain a three-dimensional intercalated HEC-PVDF-HEC high friction voltage sensing material;
[0066] Example 4
[0067] Step 1, dissolving 3 g of hydroxyethyl cellulose powder in 200 mL of aramid nanofiber dispersion at 55° C. for 30 min to obtain a 0.015 g / mL hydroxyethyl cellulose and aramid nanofiber mixed dispersion;
[0068] At 70°C, 4.5 g of polyvinylidene fluoride was dissolved in 9 mL of N,N-dimethylformamide solution and stirred at 200 r / min for 3 h to prepare the spinning solution for the electrospinning membrane.
[0069] Step 2, pouring the dispersion evenly into a polytetrafluoroethylene mold, and drying in a hot oven at 60° C. for 12 h to obtain a lower layer of hydroxyethyl cellulose film;
[0070] The spinning solution of the electrospinning membrane is electrospun to obtain a polyvinylidene fluoride film, at which the voltage is 16KV, the temperature is 40°C, the humidity is 70, the spinning rate of the spinning solution is 0.010mL / min, and the spinning time is 6.5h. The polyvinylidene fluoride film is obtained by electrospinning;
[0071] Step 3, gluing a polyvinylidene fluoride film on the lower hydroxyethyl cellulose film, and continuing to cast a 10 mm thick mixed dispersion of hydroxyethyl cellulose and aramid nanofibers to obtain a wet upper hydroxyethyl cellulose film, drying in a hot oven at 60° C. for 12 h, and finally drying to obtain a three-dimensional intercalated HEC-PVDF-HEC high friction voltage sensing material;
[0072] Example 5
[0073] Step 1, dissolving 3 g of hydroxyethyl cellulose powder in 200 mL of aramid nanofiber dispersion at 55° C. for 30 min to obtain a 0.015 g / mL hydroxyethyl cellulose and aramid nanofiber mixed dispersion;
[0074] At 70°C, 5 g of polyvinylidene fluoride was dissolved in 9 mL of N,N-dimethylformamide solution and stirred at 200 r / min for 3 h to prepare the spinning solution for the electrospinning membrane.
[0075] Step 2, pouring the dispersion evenly into a polytetrafluoroethylene mold, and drying in a hot oven at 60° C. for 12 h to obtain a lower layer of hydroxyethyl cellulose film;
[0076] The spinning solution of the electrospinning membrane is electrospun to obtain a polyvinylidene fluoride film, at which the voltage is 17KV, the temperature is 45°C, the humidity is 65%, the spinning solution spinning rate is 0.010mL / min, and the spinning time is 7h. The polyvinylidene fluoride film is obtained by electrospinning;
[0077] Step 3, gluing a polyvinylidene fluoride film on the lower hydroxyethyl cellulose film, and continuing to pour a 10 mm thick mixed dispersion of hydroxyethyl cellulose and aramid nanofibers to obtain a wet upper hydroxyethyl cellulose film, drying in a hot oven at 60° C. for 12 hours, and finally drying to obtain a three-dimensional intercalated HEC-PVDF-HEC high friction voltage sensing material.
[0078] Table 1 Technical parameters of high friction voltage sensing materials obtained in Examples 1 to 5
[0079]
[0080] In the friction voltage test, the HEC-PVDF-HEC high friction voltage sensor material was first cut into 5*5cm square pieces, and then copper foil tape and wires were attached to the back of the material in a grid structure to prepare the positive electrode device of the friction nanogenerator. In the same way, the negative electrode device of the friction nanogenerator was prepared using polytetrafluoroethylene film. The positive and negative electrode materials were connected to an oscilloscope, and a linear motor was used to give a uniform and stable impact force to make the positive and negative electrodes contact and separate, causing charge transfer and generating friction voltage.
[0081] Table 1 shows the technical parameters of the high friction voltage sensing materials prepared in Examples 1 to 5. It can be seen that the friction power generation positive electrode material prepared by the process route provided by the present invention benefits from the introduction of aramid nanofibers to enhance its toughness and strength, and its mechanical strength is in the range of 10-15MPa. As the concentration of hydroxyethyl cellulose increases, the HEC-PVDF-HEC film becomes thicker and thicker, and its mechanical strength becomes higher and higher. The friction voltage is greatly affected by the thickness of the hydroxyethyl film. The thicker the positive electrode material, the stronger the electrostatic coupling charge transfer ability, the more electrons are lost, the greater the potential difference between the positive and negative electrodes, and the greater the friction voltage. Similarly, the wide bandgap charge retention phase PVDF film effectively improves the accumulation and transmission efficiency of the charge, and also improves the friction voltage output by the material. This structural design not only enhances the overall performance of the material, but also improves the output stability and sensitivity of the nano friction generator.
[0082] Figures 3 to 7The friction voltage of the high friction voltage hydroxyethyl cellulose sensing material prepared in Examples 1 to 5 is used to prepare a 5*5 cm square friction power generation device by using a polytetrafluoroethylene film as the negative electrode. Different output voltages can be generated by applying forces of different magnitudes. It can be used for flexible wear and can sense different activities of the human body by monitoring the different output voltages.
[0083] The present invention also discloses a nano friction power generation device prepared by connecting a high friction voltage hydroxyethyl cellulose sensing material and polytetrafluoroethylene. The microcurrent generated by electrostatic coupling can light up the TENG small lamp.
[0084] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.
Claims
1. A high friction voltage hydroxyethyl cellulose sensing material, characterized in that: The invention comprises a three-layer structure, which comprises respectively an upper hydroxyethyl cellulose film, a polyvinylidene fluoride film and a lower hydroxyethyl cellulose film from top to bottom.
2. A method for preparing a high friction voltage hydroxyethyl cellulose sensing material, characterized in that: The following steps are involved: Step 1, preparing a mixed dispersion of hydroxyethyl cellulose and aramid nanofibers and a spinning solution containing polyvinylidene fluoride; Step 2, the mixed dispersion of hydroxyethyl cellulose and aramid nanofibers is cast and dried to obtain a lower hydroxyethyl cellulose film; The spinning solution containing polyvinylidene fluoride is spun by electrostatic spinning to obtain a polyvinylidene fluoride film; Step 3, placing the polyvinylidene fluoride film on the upper surface of the dried lower hydroxyethyl cellulose film; Then, on the upper surface of the polyvinylidene fluoride film, a wet upper hydroxyethyl cellulose film is prepared by using a casting method using a mixed dispersion of hydroxyethyl cellulose and aramid nanofibers; and then a three-dimensional intercalated HEC-PVDF-HEC high friction voltage sensing material is obtained through drying.
3. The method for preparing a high friction voltage hydroxyethyl cellulose sensing material according to claim 2, characterized in that: In step 1, the preparation method of the mixed dispersion of hydroxyethyl cellulose and aramid nanofibers is as follows: 2 to 3 g of hydroxyethyl cellulose powder is dissolved in 200 to 300 mL of aramid nanofiber dispersion at 45 to 55° C. for 20 to 30 min to obtain a mixed dispersion of hydroxyethyl cellulose and aramid nanofibers; wherein the viscosity of the hydroxyethyl cellulose is 2600 to 3300 mPa.s, and the concentration of the hydroxyethyl cellulose dispersion is 0.010 to 0.015 g / mL.
4. The method for preparing a high friction voltage hydroxyethyl cellulose sensing material according to claim 3, characterized in that: The preparation of the aramid nanofiber mixed dispersion is as follows: first, an alkaline solution, para-aramid fibers and dimethyl sulfoxide are stirred and mixed to obtain a dispersion A; wherein the mass ratio of the para-aramid fibers to the dimethyl sulfoxide is 2-3:200-300, the solute of the alkaline solution is potassium hydroxide, the concentration of the solute in the alkaline solution is 0.3-0.6 g / mL, and the ratio of the alkaline solution to the para-aramid fibers is 1-2 mL:2-3 g; Dispersion A is evenly dispersed in deionized water, and then filtered to obtain para-aramid nanofiber dispersion B; wherein the volume ratio of water to dispersion A is 1000-1500:50-100, and the concentration of the para-aramid nanofiber dispersion is 1%-1.5%.
5. The method for preparing a high friction voltage hydroxyethyl cellulose sensing material according to claim 2, characterized in that: In step 1, the spinning solution containing polyvinylidene fluoride is prepared as follows: polyvinylidene fluoride is dissolved in N,N-dimethylformamide solution to obtain the spinning solution.
6. The method for preparing a high friction voltage hydroxyethyl cellulose sensing material according to claim 5, characterized in that: The ratio of polyvinylidene fluoride and N, N-dimethylformamide solution is 4-5g:7-9mL, the dissolution temperature is 60-70°C, the rotation speed is 100-200r / min, and the time is 2-3h.
7. The method for preparing a high friction voltage hydroxyethyl cellulose sensing material according to claim 2, characterized in that: In step 2, during the preparation of the lower hydroxyethyl cellulose film, the drying temperature is 60-70° C., the drying time is 10-12 hours, and the film thickness of the lower hydroxyethyl cellulose film after drying is 0.06-0.08 mm.
8. The method for preparing a high friction voltage hydroxyethyl cellulose sensing material according to claim 2, characterized in that: In step 2, during the electrospinning process, the voltage is 15-17 kV, the temperature is 35-45° C., the humidity is 65%-75%, the spinning liquid spinning rate is 0.008-0.010 mL / min, and the time is 6-8 h.
9. The method for preparing a high friction voltage hydroxyethyl cellulose sensing material according to claim 2, characterized in that: In step 3, during the drying process, the temperature is 60-70° C., the time is 10-12 hours, and the film thickness of the upper hydroxyethyl cellulose film after drying is 0.06-0.08 mm.
10. A grid-structured friction nano-power generation device prepared from the high friction voltage hydroxyethyl cellulose sensing material according to claim 1.
Citation Information
Patent Citations
Fiber base multilayer structure friction nanometer power generator and preparation method thereof
CN108616225A
ANF-reinforced HEC film composite material and preparation method thereof
CN110964216A
Cellulose-based nano friction generator with high output performance and preparation method thereof
CN114221573A
Preparation method and application of piezoelectric-triboelectric coupling induction material
CN114539574A
Micro-nano composite electret film for micro-energy collection and manufacturing method of micro-nano composite electret film
CN116160744A
Cited By
Hydroxyethyl cellulose-aramid fiber / MXene nanometer friction positive electrode material and preparation method thereof
CN119708589A
